Kontribusi Data Akuntansi Biaya terhadap Peningkatan Nilai Perusahaan dan Tanggung Jawab Pemangku Kepentingan pada Perusahaan Manufaktur Semen Indonesia - Lismawati, Lismawati; Hardana, Ali; Utami, Try Wahyu; Mutiah, Nur (Institut Agama Islam Negeri Ponorogo, 2023)
Introduction: The purpose of this study is to determine the effect of cost accounting information on the improvement of corporate value and responsibility to stakeholders, at cement industry companies listed in Indonesia Stock Exchange (BEI) period 2016-2021. Research Methods: Data analysis techniques using simple linear regression analysis product correlation moment for causality test and comparative analysis k one way ANOVA independent sample for comparative test, with 5% significance level. Results: The results showed that the cost accounting information, which is realized in the calculation of cost of goods manufactured, has a significant effect on the increase of company value. Increased corporate value significantly influences the company's ability to fulfill its responsibilities to stakeholders, such as paying dividends to shareholders, borrowing interest expense to creditors, hiring employees and paying taxes to the government. Conclusion: This study also concludes that there are differences of firm size, dividend payout, tax burden, interest expense on cement company go public in Indonesia, while the salary load is not significant difference.